COMPARATIVE CHARACTERISTICS OF SURGICAL TREATMENT METHODS OF GENITAL PROLAPSE - Dudchenko, Varvara; Hromova, Antonina (Eastern Ukrainian Medical Journal, 2025)
Introduction. Genital prolapse or pelvic floor dysfunction is a common pathology among the female population. One in three patients requires surgical treatment, which causes a deterioration in their quality of life. Given the variety of surgical methods for treating this pathology, studying their impact on women's health to improve them is relevant and requires further research.The aim of the study – a comparative assessment of various methods of surgical treatment of genital prolapse.Materials and Methods: 73 patients were examined: Group I – 21 patients with genital prolapse, who underwent laparoscopically assisted hysterectomy with appendages and colpoperineorrhaphy with levatoroplasty, Group II – 22 women, who underwent vaginal extirpation of the uterus with appendages and colpoperineorrhaphy with levatoroplasty, and Group III – 30 women, who underwent video-assisted total hysterectomy with appendages and bilateral fixation of the vaginal stump, and in case of prolapse of the III–IV degree – additionally colpoperineorrhaphy and levatoroplasty. The method of surgical treatment was chosen taking into account the severity of extragenital pathology and contraindications to the use of pneumoperitoneum in laparoscopic operations.Results and Discussion. Analyzing the volume and type of surgical intervention by groups, it was noted that vaginal extirpation of the uterus with appendages with colpoperineorrhaphy and levatoroplasty was performed predominantly in cases of complete vaginal prolapse, in women of an older age group and with more pronounced extragenital diseases. While laparoscopically assisted hysterectomy with appendages was performed mainly in cases of complete or incomplete genital prolapse and with compensated forms of extragenital diseases. Laparoscopic total hysterectomy with appendages and bilateral fixation of the vaginal stump is used both in the initial stages of prolapse and in cases of complete prolapse of the uterus (in combination with colpoperineorrhaphy and levatoroplasty) and has a better therapeutic effect due to the minimization of intraoperative complications. Also, total laparoscopic hysterectomy with appendages and bilateral fixation of the vaginal stump has advantages compared to groups I and II due to the possibility of performing any other concomitant operations: laparoscopic cholecystectomy, laparoscopic appendectomy, laparoscopic cystectomy of various localizations, viscerolysis in any floor of the abdominal cavity.Conclusions. Accurate diagnosis and personalized selection of treatment tactics for genital prolapse contribute to increasing the effectiveness of surgical treatment and reducing disease recurrence. The use of the latest video laparoscopic technologies allows for improved visualization, thereby reducing intra- and postoperative complications, allows for combined surgical interventions, which is economically feasible and reduces the psychological burden on the patient. The use of estriol-containing drugs contributes to better healing of postoperative sutures, thereby increasing the effectiveness of surgical treatment of genital prolapse and minimizing recurrences of this disease, and treats genitourinary syndrome.